VERBA TURUNAN DALAM BAHASA JAWA - Siti Mulyati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe the affixation process, semantic change in the formation of derived verbals, and the functions that such verbals can serve in Javanese sentences. It employed the descriptive approach. The data were collected from sentences the Djaka Lodang magazine and spoken discourse in society. They were collected through reading, listening, and recording. The data were analyzed using the substitution method. The findings show that derived verbals in Javanese can be formed using prefixes N-, maN-, ka-, ke-, di-/ dipun-, and bawa ha, infixes -um- and -in-,suffixes -i, -a, -en, –an, -na, -ana, and -ake/-aken, confix ka-/ -an, and combined affixes N-/ -i, N-/ -ake, N- / -a, N- / -na, N-/ -ana, di-/ -i, di- / -a, di- / -na, di- / ake, -in-/ -an, -in-/ -ake, -in-/ -ana, and -um- / -a. Derived verbs in Javanese can be both active verbs and passive verbs. They can function as subjects, predicates, objects, complements, or adverbials in sentences.